2019
DOI: 10.1371/journal.pntd.0007435
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of new hosts with human trade shapes the extant distribution of Toxoplasma gondii lineages

Abstract: Toxoplasma gondii is a zoonotic protozoan with a worldwide occurrence, but the determinants of the current pattern in the geographical distribution of T . gondii lineages and strains remain poorly understood. To test the influence of human trade on T . gondii populations, we conducted a population genetic study of 72 T . gondii animal isolates from Senegal, a West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 52 publications
(69 reference statements)
0
39
1
Order By: Relevance
“…The detection of an Africa 4 strain isolated from a sheep for the rst time in Tunisia con rms its spread across the African continent. Strains belonging to this lineage (Africa 4) have been repeatedly isolated from immune-suppressed African patients in France 24 and more recently in poultry and rodents from Senegal, West Africa 4,38 . Other studies using RFLP markers showed the circulation of this lineage (RFLP genotypes of this lineage are known under the designation of ToxoDB # 20 and ToxoDB#137) in the Emirates, China, Sri Lanka as well as in East Africa 23,24,39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of an Africa 4 strain isolated from a sheep for the rst time in Tunisia con rms its spread across the African continent. Strains belonging to this lineage (Africa 4) have been repeatedly isolated from immune-suppressed African patients in France 24 and more recently in poultry and rodents from Senegal, West Africa 4,38 . Other studies using RFLP markers showed the circulation of this lineage (RFLP genotypes of this lineage are known under the designation of ToxoDB # 20 and ToxoDB#137) in the Emirates, China, Sri Lanka as well as in East Africa 23,24,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasma gondii is a zoonotic apicomplexan parasite infecting humans and other warm-blooded animals including livestock 1,2 and poultry 3,4 . The latters serve as an intermediate host, while felines are the nal hosts of T. gondii 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Heart and brain were collected, preserved at 4°C or on ice and processed at the ISBA laboratory (Cotonou) within the next five days. The isolation protocol on Swiss mice follows the description by Galal and collaborators in 2019 [ 4 ]. Cryogenized tissue samples of seropositive mice were then stored in liquid nitrogen at the T .…”
Section: Methodsmentioning
confidence: 99%
“…Other ground-foraging animals, such as poultry, are good bioindicators of T . gondii circulation in the environment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation